Disrupted body-image and pregnancy-related lumbopelvic pain. A preliminary investigation - Wand, B.; Elliott, R.; Sawyer, A.; Spence, R.; Beales, Darren; O'Sullivan, Peter; Smith, Anne; Gibson, W. (2017)
Background: Recent investigations have suggested that disrupted body-image may contribute to the lumbopelvic pain experience. The changes in body shape and size associated with pregnancy suggest that pregnancy-related lumbopelvic pain might be a problem in which alterations in body-image are particularly relevant. Objectives: To investigate if self-reported body-image is related to lumbopelvic pain status in women during pregnancy and explore the factors that might contribute to changes in body-image in women experiencing pregnancy-related lumbopelvic pain. Design: Cross-sectional cohort study. Method: Forty-two women in the third trimester of pregnancy were recruited regardless of clinical status. Pain intensity and disability were measured to estimate clinical severity. The Fremantle Back Awareness Questionnaire was used to assess body-image. Participants also completed a series of questionnaires and physical tests to explore factors that might be associated with altered body-image. Results: The median Fremantle Back Awareness Questionnaire score for the pain free women was 1 (IQR 0–1.5) and the median score for those in pain was 3.5 (IQR 2–8). This difference was statistically significant (p = 0.005). The questionnaire score was significantly correlated with pain intensity but not with disability. Of the measured variables only pain catastrophisation was significantly associated with disrupted body-image. Conclusions: Self-reported disruption of body-image was significantly greater in pregnant women who were experiencing lumbopelvic pain than those who weren't and the extent of body-image disruption was associated with pain intensity. Only pain related catastrophisation was related to disrupted body-image.